Preparation method of porous silicon-carbon material with silicon-copper alloy as supporting structure as well as product and application of porous silicon-carbon material
By using silicon copper alloy as a porous silicon carbon material in the lithium-ion battery negative electrode material, the problems of increased stress caused by volume expansion of the silicon negative electrode material and attenuation of battery capacity are solved, and the high cycle stability and excellent electrochemical performance of the material are achieved.
Patent Information
- Application Number
- CN202411818408.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The large-scale application of silicon as a negative electrode material for lithium-ion batteries is hindered by the huge volume changes in the embeddedness and release of lithium ions during the battery operation, resulting in an increase in the internal stress of the negative electrode, some electrode materials are powdered, and the battery capacity is rapidly attenuated.
Silicon copper alloy is used as the supporting structure, silicon particles are riveted on the copper particles through high-energy ball milling method, and a porous silicon copper oxide material is generated in combination with a heat treatment process, and a polyacrylonitrile layer is introduced through the carbonization method to form a porous silicon carbon material supported by the silicon copper alloy.
The electrochemical performance and structural stability of the material are significantly improved. Through the synergistic effect of internal pores and support structures, the embedding and disengagement efficiency of Li+ is improved, the volume expansion during the charging and discharging process is buffered, and the cycle life of the battery is extended.
Smart Images

Figure CN119650643A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion batteries, and particularly relates to a preparation method of a porous silicon-carbon material with a silicon-copper alloy as a supporting structure, a product thereof, and an application thereof as a negative electrode material for lithium ion batteries. Background Art
[0002] Since Sony first commercialized lithium-ion batteries in 1991, they have been recognized as the cornerstone of energy storage and conversion. Over the past three decades, conventional lithium-ion batteries have struggled to meet the growing demands of consumer electronics, electric vehicles, and large-scale energy storage systems. However, the electrochemical performance of lithium-ion batteries is limited by the electrode materials, so seeking an electrode material with high specific capacity is the key to improving the energy density of batteries.
[0003] The theoretical specific capacity of graphite, the mainstream negative electrode material on the market, is only 372mAh g-1. Traditional graphite negative electrodes can no longer meet the commercial needs of existing lithium-ion batteries. Among the existing negative electrode candidate materials, silicon is considered to be one of the most promising new negative electrode materials for high-energy-density lithium-ion batteries due to its abundant crustal reserves, extremely high theoretical specific capacity (4200mAh g-1) and good environmental compatibility. However, the large-scale application of silicon as a negative electrode material still faces huge challenges. During the operation of the battery, that is, the process of lithium ion insertion and extraction, huge volume changes occur. The drastic volume expansion will cause greater stress inside the negative electrode, and eventually part of the electrode material will pulverize, causing the battery capacity to decay rapidly, becoming the biggest obstacle to its commercial development.
[0004] Therefore, how to effectively suppress the expansion of silicon negative electrodes has become a difficult problem that the lithium battery industry needs to overcome urgently, and this technical field needs to be improved in terms of materials and processes. Summary of the invention
[0005] In view of this, one of the purposes of the present invention is to provide a method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure; the second purpose of the present invention is to provide a porous silicon-carbon material with a silicon-copper alloy as a supporting structure; the third purpose of the present invention is to provide an application of a porous silicon-carbon material with a silicon-copper alloy as a supporting structure in lithium-ion battery negative electrode materials. The synergistic effect of the silicon-copper alloy obtained by the method and the pores of the heat treatment process can achieve good cycle stability of the material.
[0006] The technical solution of the present invention is:
[0007] A method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure comprises the following steps:
[0008] (1) dispersing silicon powder and copper powder in anhydrous ethanol to form a suspension;
[0009] (2) adding ethylene glycol to the suspension in step (1), and mixing them uniformly by high-energy ball milling to initially rivet the silicon particles onto the copper particles;
[0010] (3) heating the product obtained in step (2) in a water bath to evaporate anhydrous ethanol, and removing ethylene glycol by vacuum drying to obtain a silicon-copper mixture;
[0011] (4) heating the silicon-copper mixture obtained in step (3) in a muffle furnace and cooling in air to obtain a silicon-copper oxide mixture;
[0012] (5) dissolving polyacrylonitrile in N-(N-dimethylformamide) by heating in a water bath and stirring to form a polyacrylonitrile solution;
[0013] (6) adding the copper oxide silicon mixture prepared in step (4) to the polyacrylonitrile solution prepared in step (5), and evaporating the N-N-dimethylformamide by heating in an oil bath to obtain a precursor powder;
[0014] (7) The precursor powder obtained in step (6) is carbonized in a tubular furnace in an argon atmosphere to obtain a silicon-carbon material with a silicon-copper alloy as a supporting structure.
[0015] Preferably, in step (1), the particle size of the silicon powder is 30-60 nm, the particle size of the copper powder is 5-20 μm, the mass ratio of silicon powder to copper powder is 2-10:1, and the mass and volume ratio of silicon powder to copper powder to anhydrous ethanol is 0.02-0.1 g: 0.01-0.1 g: 40-80 ml.
[0016] Preferably, in step (2), the volume ratio of ethylene glycol to suspension is 2-6 ml:40-80 ml, the high-energy ball milling time is 2-5 h, the rotation speed is 200-500 rpm, and the ball-to-material ratio is 30:1.
[0017] Preferably, in step (3), the water bath heating temperature is 85-95° C., the vacuum drying temperature is 70-90° C., and the time is 8 hours.
[0018] Preferably, in step (4), the temperature of the muffle furnace is 250-350° C., and the heating time is 10 to 60 minutes.
[0019] Preferably, in step (5), the mass volume ratio of the polyacrylonitrile and NN dimethylformamide solution is 20-100:10-50, mg:ml, the water bath heating temperature is 70-80°C, and the stirring speed is 100-200 rpm.
[0020] Preferably, in step (6), the mass volume ratio of the copper silicon oxide mixture to the polyacrylonitrile solution is 0.05-0.15 g:10-30 ml, the oil bath heating temperature is 170-190° C., and the stirring speed is 100-200 rpm.
[0021] Preferably, in step (7), the carbonization conditions are “carbonization under an inert atmosphere at a temperature of 300 to 400° C. for 1 to 2 h, and carbonization under a temperature of 750 to 900° C. for 2 to 4 h.
[0022] 2. The porous silicon-carbon material using the silicon-copper alloy prepared according to the above preparation method as the supporting structure.
[0023] 3. Application of the porous silicon-carbon material with the silicon-copper alloy as a supporting structure in negative electrode materials of lithium-ion batteries.
[0024] The beneficial effects of the present invention are as follows: the present invention discloses a porous silicon-carbon material with a silicon-copper alloy as a supporting structure. The preparation of the material first utilizes the commonly used high-energy ball milling method to obtain a silicon-copper mixture, so that the silicon particles are firmly riveted on the copper particles. This step can appropriately improve the problem of low conductivity of the material. Then, a heat treatment process is used to obtain a porous silicon-copper oxide material and generate a small amount of silicon-copper alloy. Subsequently, an oil bath heating is used to introduce a polyacrylonitrile layer, and finally a one-time carbonization method is used to convert the polyacrylonitrile layer into a polyacrylonitrile-derived carbon, reducing copper oxide to copper and generating a silicon-copper alloy. The introduction of a large number of pore structures into the composite material can accelerate the embedding and extraction process of Li+ in the composite material and improve the transmission efficiency of Li+ between the electrode and the electrolyte interface. At the same time, a buffer space is provided for the volume expansion generated during the charge and discharge process, thereby significantly improving the electrochemical properties and structural stability of the material. More importantly, the silicon-copper alloy generated twice during the material preparation process serves as a support to ensure the stability of the electrode structure. According to experimental results, the porous silicon-carbon material with the silicon-copper alloy as a supporting structure has a synergistic effect of internal pores and supporting structures at 1000mA·g -1 After 120 cycles at a current density of 1.54 mAh g -1 Specific capacity.
[0025] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description.
[0026] Other advantages, objectives and features of the invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0028] Figure 1 This is the X-ray diffraction pattern of the material (Si / Cu@C) prepared in Example 1.
[0029] Figure 2 These are the specific surface area test graph and pore size distribution graph of the material (Si / Cu@C) prepared in Example 1, where (a) is the specific surface area test graph and (b) is the pore size distribution test graph.
[0030] Figure 3 This is the transmission electron microscope (TEM) image of the material (Si / Cu@C) prepared in Example 1.
[0031] Figure 4 Comparison of cycle performance test curves of lithium-ion half-cells constructed with the material prepared in Example 1 (Si / Cu@C-1), the material prepared in Example 2 (Si / Cu@C-2) and the material prepared in Example 3 (Si / Cu@C-3) as negative electrode materials at a current density of 1000mA / g.
[0032] Figure 5 Comparison of cycle performance test curves of lithium-ion half-cells constructed with the material prepared in Example 1 (Si / Cu@C-1), the material prepared in Comparative Example 1 (Si@Cu) and the material prepared in Comparative Example 2 (Si@C) as negative electrode materials at a current density of 1000 mA / g. DETAILED DESCRIPTION
[0033] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0034] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0035] Example 1
[0036] A porous silicon-carbon material with a silicon-copper alloy as a supporting structure, and a specific preparation method thereof is as follows:
[0037] (1) 0.1 g of silicon powder and 0.025 g of copper powder were placed in 50 ml of anhydrous ethanol to obtain suspension A; 3 ml of ethylene glycol was added to suspension A to obtain suspension B;
[0038] (2) B was ball-milled at a speed of 300 rpm and a ball-to-material ratio of 30 to 1 for 4 h to obtain product 1. Product 1 was placed in a water bath at a temperature of 90° C. and stirred at a speed of 300 rpm for 30 min to obtain product 2. Product 2 was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a silicon-copper mixture.
[0039] (3) The silicon-copper mixture obtained in step (2) is placed in a muffle furnace at 600° C. and heated for 30 min, and then cooled in air to obtain a silicon-copper oxide mixture having a porous structure.
[0040] (4) 0.068 g of polyacrylonitrile was placed in 34 ml of N-N-dimethylformamide, and then stirred at 70° C. and 200 rpm. After stirring for 20 min, the copper oxide mixture obtained in step (3) was added and stirred for 20 min to obtain product 3.
[0041] (5) The product 3 was stirred at 175° C. and 200 rpm, and after the liquid evaporated, a polyacrylonitrile layer-coated copper oxide silicon material was obtained.
[0042] (6) The polyacrylonitrile layer-coated silicon copper oxide material obtained in step (5) is placed in a tubular furnace into which argon gas is introduced, and then the temperature is raised to 300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours. Then, the temperature is raised to 850°C at a heating rate of 5°C / min to obtain a porous silicon-carbon material with a silicon-copper alloy as a supporting structure. This material is labeled as (Si / Cu@C)1.
[0043] Example 2
[0044] A porous silicon-carbon material with a silicon-copper alloy as a supporting structure, and a specific preparation method thereof is as follows:
[0045] (1) 0.1 g of silicon powder and 0.025 g of copper powder were placed in 50 ml of anhydrous ethanol to obtain suspension A; 3 ml of ethylene glycol was added to suspension A to obtain suspension B;
[0046] (2) B was ball-milled at a speed of 300 rpm and a ball-to-material ratio of 30 to 1 for 4 h to obtain product 1. Product 1 was placed in a water bath at a temperature of 90° C. and stirred at a speed of 300 rpm for 30 min to obtain product 2. Product 2 was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a silicon-copper mixture.
[0047] (3) The silicon-copper mixture obtained in step (2) is placed in a muffle furnace at 600° C. and heated for 30 min, and then cooled in air to obtain a silicon-copper oxide mixture having a porous structure.
[0048] (4) 0.058 g of polyacrylonitrile was placed in 29 ml of N-N-dimethylformamide, and then stirred at 70° C. and 200 rpm. After stirring for 20 min, the copper oxide mixture obtained in step (3) was added and stirring was continued for 20 min to obtain product 3.
[0049] (5) The product 3 was stirred at 175° C. and 200 rpm, and after the liquid evaporated, a polyacrylonitrile layer-coated copper oxide silicon material was obtained.
[0050] (6) The polyacrylonitrile layer-coated silicon copper oxide material obtained in step (5) is placed in a tubular furnace into which argon gas is introduced, and then the temperature is raised to 300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours. Then, the temperature is raised to 850°C at a heating rate of 5°C / min to obtain a porous silicon-carbon material with a silicon-copper alloy as a supporting structure. This material is labeled as (Si / Cu@C)2.
[0051] Example 3
[0052] A porous silicon-carbon material with a silicon-copper alloy as a supporting structure, and a specific preparation method thereof is as follows:
[0053] (1) 0.1 g of silicon powder and 0.025 g of copper powder were placed in 50 ml of anhydrous ethanol to obtain suspension A; 3 ml of ethylene glycol was added to suspension A to obtain suspension B;
[0054] (2) B was ball-milled at a speed of 300 rpm and a ball-to-material ratio of 30 to 1 for 4 h to obtain product 1. Product 1 was placed in a water bath at a temperature of 90° C. and stirred at a speed of 300 rpm for 30 min to obtain product 2. Product 2 was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a silicon-copper mixture.
[0055] (3) The silicon-copper mixture obtained in step (2) is placed in a muffle furnace at 600° C. and heated for 30 min, and then cooled in air to obtain a silicon-copper oxide mixture having a porous structure.
[0056] (4) 0.078 g of polyacrylonitrile was placed in 39 ml of N-N-dimethylformamide, and then stirred at 70° C. and 200 rpm. After stirring for 20 min, the copper oxide mixture obtained in step (3) was added and stirring was continued for 20 min to obtain product 3.
[0057] (5) The product 3 was stirred at 175° C. and 200 rpm, and after the liquid evaporated, a polyacrylonitrile layer-coated copper oxide silicon material was obtained.
[0058] (6) The polyacrylonitrile layer-coated silicon copper oxide material obtained in step (5) is placed in a tubular furnace into which argon gas is introduced, and then the temperature is raised to 300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours. Then, the temperature is raised to 850°C at a heating rate of 5°C / min to obtain a porous silicon-carbon material with a silicon-copper alloy as a supporting structure. This material is labeled as (Si / Cu@C)3.
[0059] Comparative Example 1
[0060] The Si / Cu negative electrode material for lithium-ion batteries (abbreviated as Si / Cu) is prepared by riveting silicon particles on copper particles by ball milling. The specific preparation method is as follows:
[0061] (1) 0.1 g of silicon powder and 0.025 g of copper powder were placed in 50 ml of anhydrous ethanol to obtain suspension A; 3 ml of ethylene glycol was added to suspension A to obtain suspension B;
[0062] (2) B was ball-milled at a speed of 300 rpm and a ball-to-material ratio of 30 to 1 for 4 h to obtain product 1. Product 1 was placed in a water bath at a temperature of 90°C and stirred at a speed of 300 rpm for 30 min to obtain product 2. Product 2 was placed in a vacuum oven at 80°C and dried for 8 h to obtain a silicon-copper mixture, which was labeled as Si / Cu.
[0063] Comparative Example 2
[0064] The Si / C negative electrode material for lithium-ion batteries (abbreviated as Si / C) is prepared by introducing a polyacrylonitrile layer outside the silicon particles and then carbonizing the polyacrylonitrile by a one-step carbonization method. The specific preparation method is as follows:
[0065] (1) 0.068 g of polypropylene was placed in 34 ml of N-N-dimethylformamide, and then stirred at 70°C and 200 rpm for 20 min. Subsequently, 0.125 g of silicon powder was added, and stirring was continued for 20 min to obtain a dispersion.
[0066] (2) The dispersion obtained in step (1) is stirred at 175° C. and 200 rpm to obtain a precursor powder containing a polyacrylonitrile layer after the liquid evaporates.
[0067] (3) The polyacrylonitrile layer-coated precursor powder obtained in step (2) is placed in a tubular furnace into which argon gas is introduced, and then the temperature is raised to 300° C. at a heating rate of 5° C. / min and kept at this temperature for 2 h. The polyacrylonitrile-derived carbon-coated silicon material is then obtained by raising the temperature to 850° C. at a heating rate of 5° C. / min, and the material is labeled as Si@C.
[0068] Performance Testing
[0069] X-ray diffraction analysis was performed on the prepared silicon-copper-carbon material Si / Cu@C1. Figure 1 It can be seen that silicon-copper alloy is generated in the composite material.
[0070] The specific surface area and pore size distribution of the prepared silicon-copper-carbon material Si / Cu@C1 were tested. Figure 2 (a) shows the specific surface area of Si / Cu@C. It can be seen that the composite material has a smaller specific surface area (33.758 m 2 / g); Figure 2 (b) shows the pore size distribution in the material, and it can be seen that the material has a large number of micropores around 0.5nm and a small number of micropores between 0.5nm and 1nm.
[0071] The prepared silicon-copper-carbon material Si / Cu@C1 was tested by TEM. Figure 3 It can be seen that there are many light and dark stripes in the material, which is the pore structure produced by a special heat treatment process.
[0072] Investigating the electrochemical properties of the porous silicon-carbon material Si / Cu@C prepared in Examples 1-3 using the silicon-copper alloy as the supporting structure
[0073] The materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as negative electrode materials of lithium-ion batteries, and metal lithium sheets were used as positive electrode materials of lithium-ion batteries to construct lithium-ion half-cells (wherein the separator was celgard 2500, the electrolyte was composed of 1.0M LiPF6 dissolved in EC, DMC and DEC (EC:DMC:DEC=25:30:45), 3% fluoroethylene carbonate (FEC) and 0.5% vinylene carbonate (VC) for stabilizing the SEI film, and the amount of electrolyte used in the assembly of one battery was about 60 μL), and then the prepared lithium-ion half-cell was tested for discharge specific capacity at a current density of 1000 mA / g, and the experimental results corresponded to Figure 4 and Figure 5 , organize the test data into Table 1:
[0074] Table 1 Discharge capacity of the first and cycled half-cells constructed with different negative electrode materials at a certain current density
[0075]
[0076] It can be seen from Table 1 that after 120 cycles, the capacity retention rate of Example 1 is as high as 92.94%, while that of Comparative Example 1 is 27.72% and that of Comparative Example 2 is 53.97%. The above results show that the introduction of copper into the material and the use of a special heat treatment process to obtain a silicon-copper alloy and a porous structure are of great significance for improving the cyclic stability of the material. The serious volume expansion effect of silicon-based negative electrode materials is solved, and at the same time, a carbon layer is coated on the surface of the silicon particles by carbonization, which greatly improves the problem of poor conductivity of the material. Ultimately, the prepared porous silicon-carbon negative electrode material has excellent electrochemical properties and has great commercial value in the negative electrode of lithium-ion batteries.
[0077] In summary, the present invention provides a method for preparing and applying a porous silicon-carbon material with a silicon-copper alloy as a supporting structure. During the preparation process of the material, copper particles are introduced and silicon is riveted on the copper, and a silicon-copper alloy is generated to produce a large number of pores, which solves the serious volume expansion effect of silicon-based negative electrode materials. At the same time, a carbon layer is coated on the surface of silicon particles by carbonization, which greatly improves the problem of poor conductivity of the material, and finally the porous silicon-carbon material with the prepared silicon-copper alloy as a supporting structure has excellent electrochemical properties and has great commercial value in the negative electrode of lithium-ion batteries.
Claims
1. A method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure, characterized in that: The steps include: (1) dispersing silicon powder and copper powder in anhydrous ethanol to form a suspension; (2) adding ethylene glycol to the suspension in step (1), and mixing them uniformly by high-energy ball milling to initially rivet the silicon particles onto the copper particles; (3) heating the product obtained in step (2) in a water bath to evaporate anhydrous ethanol, and removing ethylene glycol by vacuum drying to obtain a silicon-copper mixture; (4) heating the silicon-copper mixture obtained in step (3) in a muffle furnace and cooling in air to obtain a silicon-copper oxide mixture; (5) dissolving polyacrylonitrile in N-(N-dimethylformamide) by heating in a water bath with stirring to form a polyacrylonitrile solution; (6) adding the copper oxide silicon mixture prepared in step (4) to the polyacrylonitrile solution prepared in step (5), and evaporating the N-N-dimethylformamide by heating in an oil bath to obtain a precursor powder; (7) The precursor powder obtained in step (6) is carbonized in a tubular furnace in an argon atmosphere to obtain a silicon-carbon material with a silicon-copper alloy as a supporting structure.
2. The method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure according to claim 1, characterized in that: In step (1), the particle size of the silicon powder is 30-60 nm, the particle size of the copper powder is 5-20 μm, the mass ratio of silicon powder to copper powder is 2-10:1, and the mass and volume ratio of silicon powder to copper powder and anhydrous ethanol is 0.02-0.1 g: 0.01-0.1 g: 40-80 ml.
3. The method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure according to claim 1, characterized in that: In step (2), the volume ratio of ethylene glycol to suspension is 2-6 ml:40-80 ml, the high-energy ball milling time is 2-5 h, the rotation speed is 200-500 rpm, and the ball-to-material ratio is 30:
1.
4. The method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure according to claim 1, characterized in that: The water bath heating temperature in step (3) is 85-95° C., and the vacuum drying temperature is 70-90° C. for 8 hours.
5. The method for preparing a porous silicon-carbon material with a silicon-copper alloy as a supporting structure according to claim 1, characterized in that: In step (4), the temperature of the muffle furnace is 250-350° C., and the heating time is 10 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: In step (5), the mass volume ratio of the polyacrylonitrile and NN dimethylformamide solution is 20-100:10-50, mg:ml, the water bath heating temperature is 70-80°C, and the stirring speed is 100-200 rpm.
7. The preparation method according to claim 1, characterized in that: In step (6), the mass volume ratio of the copper silicon oxide mixture to the polyacrylonitrile solution is 0.05-0.15 g:10-30 ml, the oil bath heating temperature is 170-190° C., and the stirring speed is 100-200 rpm.
8. The preparation method according to claim 1, characterized in that: In step (7), the carbonization conditions are "carbonization under an inert atmosphere at a temperature of 300 to 400° C. for 1 to 2 h, and carbonization under a temperature of 750 to 900° C. for 2 to 4 h.
9. A porous silicon-carbon material using the silicon-copper alloy prepared by the preparation method according to any one of claims 1 to 8 as a supporting structure.
10. Use of the porous silicon-carbon material with the silicon-copper alloy as a supporting structure in the negative electrode material of lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of silicon-carbon cathode material, silicon-carbon cathode material and lithium ion battery
CN107507972A
Preparation method of C@Cu@Si composite porous negative electrode material of lithium ion battery
CN112670488A
Preparation method and application of novel silicon-based composite porous negative electrode material of lithium ion battery
CN112885997A
Preparation method of carbon-coated silicon-copper alloy negative electrode material of lithium ion battery
CN115954443A
Dispersion-strengthened porous silicon negative electrode material as well as preparation method and application thereof
CN117088373A